Improving performance through cost allocation* - COHEN, SUSAN I.; LOEB, MARTIN (Contemporary Accounting Research, 1988)
This paper considers an intrafirm resource allocation model with a single principal and n agents. Each agent represents a division manager who uses a centrally provided input together with other inputs, including effort, to produce and sell final products. The principal represents an owner who is responsible for providing an input to the divisions. It is assumed that each agent (division manager) knows the local profit function for the division and has disutility for effort. The principal seeks to maximize firm‐wide profits net of the costs of the centrally provided input and compensation to the agents. In this setting, which incorporates divergence of preferences and asymmetric information, it is shown that the principal and the n agents can strictly improve their welfare by moving from a set of compensation functions that do not include any allocation of costs to compensation functions that are based on cost allocation. Résumé. Les auteurs se penchent sur un modèle de répartition des ressources intraentreprise en présence d'un seul mandant et de n mandataires. Chaque mandataire représente un directeur de division qui utilise un intrant, fourni par l'échelon central, en conjonction avec d'autres intrants, y inclus l'effort, pour fabriquer et vendre des produits finis. Le mandant représente un propriétaire à qui incombe la responsabilité de fournir un intrant aux divisions. L'on suppose que chaque mandataire (directeur de division) connaît la fonction de profit de sa division et a l'effort en aversion. Le mandant cherche à maximiser les profits globaux de l'entreprise, compte tenu des coûts de l'intrant fourni par l'échelon central et de la rémunération des mandataires. Dans cette situation, qui fait intervenir des préférences divergentes et de l'information asymétrique, l'on démontre que le mandant et les n mandataires peuvent strictement améliorer leur situation en passant d'un ensemble de fonctions de rémunération qui ne prévoient aucune ventilation des coûts à des fonctions de rémunération basées sur la ventilation des coûts.